PENGARUH YAKUZA TERHADAP SIKAP AMBIGU JEPANG DALAM UN CONVENTION AGAINST TRANSNATIONAL ORGANIZED CRIME TAHUN 2000 The Influence of Yakuza Toward The Japan’s Ambiguous Attitude on United Nations Conv - Danny Latif Ma'ruf (HI 16 UMY 125, 2016)
*125 Organized crime is a group that work in a structured and do criminal based business. They do some kinds of criminalism such as violence, gambling, money laundering, corruption, human, narcotics, and weapon trafficking. From those criminals an organized crime already reached wider scope as an organized crime, so that organized can be classified as a transnational organized crime because they have already got a connection with another state and especially another organized crime to make their business easily. Since they already has an international business, an organized crime need a support from their government to keep their interest working. This article tries to explain the metamorphose of yakuza as an organized crime, how can they grows and until being an transnational organized crime. This article is also tries to explain how yakuza’s movement into the politic and government system of Japan, and able to influence a foreign policy of Japan to keep their own interest and business work.